2022
DOI: 10.3390/s22176672
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection and Image Processing of Parking Space Based on Deep Learning

Abstract: The automatic parking system based on vision is greatly affected by uneven lighting, which is difficult to make an accurate judgment on parking spaces in the case of complex image information. To solve this problem, this paper proposes a parking space visual detection and image processing method based on deep learning. Firstly, a 360-degree panoramic system was designed to photograph the vehicle environment. The image has been processed to obtain a panoramic aerial view, which was input as the original image o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Huang et al [ 12 ] used Faster R-CNN and image processing techniques for parking slot detection. This is a mixed approach of object detection and traditional computer vision techniques.…”
Section: Deep Learning Parking Slot Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al [ 12 ] used Faster R-CNN and image processing techniques for parking slot detection. This is a mixed approach of object detection and traditional computer vision techniques.…”
Section: Deep Learning Parking Slot Detection Methodsmentioning
confidence: 99%
“…To achieve our goal, we will categorize the parking slot detection techniques into several distinct categories. These categories include Object Detection-Based approaches [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], which employ either Single-stage Detection or Multi-stage Detection techniques to locate the parking slot in the image. We will also explore Image Segmentation-Based techniques [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], which involve segmenting the parking slots lines from the background to achieve accurate detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are typically installed above each parking space and can detect changes in the infrared light caused by the presence of a vehicle. Video cameras [ 6 , 7 , 8 , 9 , 10 , 11 ] can be used to detect the presence or absence of a vehicle in a parking space. They are typically installed above each parking space and use image analysis software to detect changes in the video feed caused by the presence of a vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…Li Yongyi et al [21] proposed to improve artificial potential field method to complete automatic driving trajectory planning, and introduced invasive weed algorithm to solve the defects of traditional artificial potential field method. Huang C et al [22] designed a parking extraction method based on the connected region, which further simplified parking extraction and image processing. Fintzel et al [23] and Vestri et al [24] identified parking spaces from the perspective of stereo ranging; Li Yongyi.…”
Section: Introductionmentioning
confidence: 99%